Antibodies to Toxoplasma gondii in individuals with first-episode schizophrenia - Yolken, Robert H.; Bachmann, Silke; Rouslanova, Inna; Lillehoj, Erik; Ford, Glen; Torrey, Edwin F.; Schröder, Johannes (Clinical infectious diseases, 2001)
We employed enzyme immunoassay (EIA) and Western blotting techniques to measure the level of antibodies to Toxoplasma gondii proteins in serum samples from 38 individuals undergoing their first episode of schizophrenia and from a group of matched control subjects. We found that the individuals with first-episode schizophrenia had significantly increased levels of IgG, IgM, and IgA class antibodies to Toxoplasma proteins, as compared with the control subjects.
Gesehen am 07.12.2020